Smart Farming Using Arduino & GSM - Chilukuri Akanksha, Guduru Karthik, Genikani Harish Kumar, K Indrakaran Reddy , Raveendra Gudodagi (International Journal of Advanced Science and Technology, 2020)
These days agricultural field is facing lot of issues due to absence of water sources. So as to assist the farmer to overcome the problems, smart irrigation system has been utilized. In this paper, it mainly concentrates on detecting the wild animals near the border of the farm and also to save water by turning on and off the motor based on moisture content of the soil. The variables influencing the farm production and development like temperature and humidity, this system measures theses parameters periodically and are displayed on LCD. This system uses latest technology which includes cloud computing, measuring parameters are graphically represented in cloud server on time to time basis.